EFFECTIVENESS OF STATE POLICY IN WATER RESOURCES MANAGEMENT IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT OF THE AGRICULTURAL SECTOR - DRUHOVA, Olena; YERMOLENKO, Oleksii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the effectiveness of state policy in water resources management in the context of the sustainable development of the agricultural sector. The research identifies key challenges, including water resource depletion, agrochemical pollution, outdated irrigation infrastructure, insufficient investment, and the impact of climate change. The study assesses existing regulatory mechanisms and highlights their shortcomings in ensuring efficient water distribution, conservation, and environmental protection. The necessity of improving state regulation and integrating modern approaches to water use in agriculture is emphasized. A comprehensive strategy is proposed, including modernizing irrigation systems, introducing smart irrigation technologies, using artificial intelligence and remote sensing for water monitoring, and strengthening environmental regulations. The importance of integrating circular economy principles into water management, expanding public-private partnerships, and attracting international investments is underlined. Digitalization and automated water consumption control systems are also recommended to optimize resource distribution and reduce waste. The study also stresses aligning Ukraine’s water policies with European Union directives and international best practices to ensure long-term sustainability. Financial incentives, such as grants and subsidies for agricultural enterprises adopting water-saving solutions, are proposed as key mechanisms for driving change. Special attention is given to the restoration of degraded water resources, adaptation to climate change, and developing strategies to mitigate the risks of prolonged droughts and unpredictable precipitation patterns. Implementing these measures will enhance the efficiency of water management, ensure a balanced distribution of water resources, reduce environmental risks, and contribute to national food security. Sustainable water management in agriculture will help mitigate the adverse effects of climate change, preserve ecosystems, and support the competitiveness of the agricultural sector, ensuring its long-term resilience in the face of global environmental challenges.